Commons, Anti-commons, Cooperation and Fair Economy: A Reflection - Filipe, J. A. (Towards A Society with a More Fair Economy or an Economy with a More Social Face: The Contribution of Scientific Social Knowledge to the Alternative Models of Socioeconomic Development, 2015)
Capitalism has been successful as economic system. Often the system is said to be unfair; in fact entrepreneurship is awarded but in fact the economy becomes often too unfair. New practices are emerging in which situations are managed to combine merits and forms of compensation, in which the economic agents are closest to a fairer and more participatory economy involving situations of mutual direct benefit. New processes are coming to force a new vision. The present study discusses business and economic practices, some involving new dynamics and some kinds of cooperation in a larger scale than before, with new promising ways of commitment to alternative structures but sometimes being also essentially a complementary form of organization of society to the current standard.